Encapsulation of CoSx Nanocrystals into N/S Co‐Doped Honeycomb‐Like 3D Porous Carbon for High‐Performance Lithium Storage. Issue 9 (20th July 2018) - Yin, Bo; Cao, Xinxin; Pan, Anqiang; Luo, Zhigao; Dinesh, Selvakumaran; Lin, Jiande; Tang, Yan; Liang, Shuquan; Cao, Guozhong
Abstract: A honeycomb‐like 3D N/S co‐doped porous carbon‐coated cobalt sulfide (CoS, Co9 S8, and Co1– x S) composite (CS@PC) is successfully prepared using polyacrylonitrile (PAN) as the nitrogen‐containing carbon source through a facile solvothermal method and subsequent in situ conversion. As an anode for lithium‐ion batteries (LIBs), the CS@PC composite exhibits excellent electrochemical performance, including high reversible capacity, good rate capability, and cyclic stability. The composite electrode delivers specific capacities of 781.2 and 466.0 mAh g −1 at 0.1 and 5 A g −1, respectively. When cycled at a current density of 1 A g −1, it displays a high reversible capacity of 717.0 mAh g −1 after 500 cycles. The ability to provide this level of performance is attributed to the unique 3D multi‐level porous architecture with large electrode–electrolyte contact area, bicontinuous electron/ion transport pathways, and attractive structure stability. Such micro‐/nanoscale design and engineering strategies may also be used to explore other nanocomposites to boost their energy storage performance. Abstract : The honeycomb‐like 3D N/S co‐doped porous carbon‐coated cobalt sulfide (CS@PC) has porous structure, superior electronic conductivity, and high lithium ion diffusion efficiency, which guarantee the excellent electrochemical performance of the CS@PC composite. When cycling at 1 A g −1, the CS@PC electrode can deliver specific discharge capacities of 717.0 mAh g −1 after 500 cycles.